The open conformation of WASP regulates its nuclear localization and gene transcription in myeloid cells - Looi, C.Y.; Sasahara, Y.; Watanabe, Y.; Satoh, M.; Hakozaki, I.; Uchiyama, M.; Wong, W.F.; Du, W.; Uchiyama, T.; Kumaki, S.; Tsuchiya, S.; Kure, S. (Oxford University Press, 2014)
Mutations in the gene encoding the Wiskott–Aldrich syndrome protein (WASP) are responsible for Wiskott–Aldrich syndrome and WASP is a major actin regulator in the cytoplasm. Although rare gain-of-function mutations in the WASP gene are known to result in X-linked neutropenia (XLN), the molecular pathogenesis of XLN is not fully understood. In this study, we showed that all reported constitutively activating mutants (L270P, S272P and I294T) of WASP were hyperphosphorylated by Src family tyrosine kinases and demonstrated higher actin polymerization activities compared with wild-type (WT) WASP. Further analysis showed a tendency of activating WASP mutants to localize in the nucleus compared with WT or the Y291F mutant of WASP. In addition, we found that WASP could form a complex with nuclear RNA-binding protein, 54kDa (p54nrb) and RNA polymerase II (RNAP II). ChIP assays revealed that WASP associated with DNA, although the affinity was relatively weaker than RNAP II. To determine whether gene transcription was affected by WASP mutation in myeloid cells, we performed microarray analysis and found different expression profiles between WT and L270P WASP-transfected K562 cells. Among the genes affected, granulocyte colony-stimulating factor receptor, Runx1, and protein tyrosine phosphatase receptor c were included. ChIP on chip analysis of genomic DNA showed WT and L270P WASP had a highly similar DNA-binding pattern but differed in binding affinity at the same locus. Therefore, our results suggest that the open conformation of WASP regulates its nuclear localization and plays requisite roles in regulating gene transcription that would contribute to the outcome in the nucleus of myeloid cells.